Resumes de recherche 2000 (Center for International Forestry Research, 2001)
This publication is a collection of the abstracts of in-house and external publications produced in the year 2000 by CIFOR scientists and their collaborators. It also abstracts several publications produced in 1999 that were not able to be included in the 1999 research abstrats. The abstracts are grouped into six themes that represent CIFOR's research activities. Indexes are provided by author and subject.